أنماط الافادة من شبکات التواصل الاجتماعیة و المهنیة لدى عینة من أعضاء هیئة التدریس بالجامعات المصریة - د. اسماء محمد السید (المجلة الدولية لعلوم المكتبات والمعلومات)
The present study aims to study patterns of utilization of social andprofessional networks in a sample of (200) members of faculty from variousscientific and functional categories. They were selected in a deliberate mannerfrom a number of Egyptian universities, including Cairo, Ain Shams, Helwan,Menoufia and Beni Suef.The study focuses on their motivation, their needs from the social andprofessional networks, and the extent of their use in their specialties according toyears of experience and degree. The study is based on the analytical descriptiveapproach. This study is part of the descriptive studies to examine the reality ofthe modes of benefit of the faculty members from these social and professionalnetworks. The study relies on collecting the data on a questionnaire prepared bythe researcher consisting of 50 items.The study came out with the following results:1. The most commonly used age groups for social and professional networksare the youth group, a group of less than 30 years old.2. The most positive forms of participation in the study community for the use ofsocial and professional networks varied between the access to news andinformation, learning new things through social networks, free expression ofopinion, enable overcoming the barrier of shyness between students andfaculty, and holding fruitful meetings and meetings With colleagues remotely,in addition to social networks as a means of communication and informationexchange, it is one of the most important educational tools to improve theeducational process.3. The nature of the materials used by the community of beneficiaries of socialand professional networks varied between the form of text and visual andaudio.4. There is a phenomenon of Iqbal to use mobile phone as a means to enter thesocial and professional networks.5. high frequency on social and vocational networks with increasing time spenton each visit. There are a number of negative consequences of the use of social andprofessional networks, and varied between psychological and neurologicalconsequences, as it was one of the negative implications for the use offaculty members of the social networks and professional belief that they stealtime, and lead to the loss of high value, Negatives some of the physicalimplications of what we call the psychological stress, nervous and visual.7. The Facebook and Twitter network ranked first in the ranking of socialnetworks, while Linked Network ranked first in professional networking.